The Effect of Video-Based Nutrition Education on Mothers' Behavior in Selecting Animal Protein for MPASI in Sumerta Kaja Village - Pradnya Paramitha Ayu Pradnya Ida Ayu; Ida Ayu Eka Padmiari; Ni Made Yuni Gumala (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2026)
The risk factors causing stunting are very diverse, one of the factors that can influence the occurrence of stunting is the adequacy of protein and protein consumption patterns. The purpose of this study is to determine the behavior of mothers of toddlers in choosing animal protein for complementary feeding before and after nutritional education using video media in Sumerta Kaja Village. The type of research used is pure experimental research, with a design of 'Pre-test - Post-test Control Group Design', which involves conducting two tests on two groups, namely the control group and the intervention group. The total sample is 64 with inclusion criteria of mothers who have toddlers aged 6-24 months. The results show that the average knowledge score increased from 53.84 to 79.78, the average attitude score increased from 70.22 to 83.94, and the average action score increased from 63.34 to 88.31. The Wilcoxon test results indicate a significant difference before and after the intervention with a p-value of 0.000. The results of the comparison test between the two Mann Whitney test groups indicate that both those who did not receive education and those who were educated experienced an increase in scores before and after. However, providing a video led to a greater increase in knowledge, attitudes, and actions.